Splash mask formulation of tangerine (Citrus reticulata Blanco.) peel extract and turmeric (Curcuma longa L) extract as a whitening agent - Sriarumtias, Framesti Frisma; Auliasari, Nurul (International Journal of Research in Dermatology, 2020)
Background: Indonesia is a tropical country that is exposed to the sun for 12 hours, one of the harm effects of sunlight which is damage to the skin. The purpose of this study was to determine tyrosinase inhibition of tangerin peel extract (Citrus reticulata Blanco.) from Garut, West Java, Indonesia then develop the splash mask from the extract. Methods: The tangerine peel will be extracted by maceration method. The splash mask formulation containing tangerine peel extract which has a whitening agent. Tyrosinase inhibition determine by ELISA method with tyrosinase enzyme and L-DOPA substrat. Results: The results showed that tangerine peel extract had tyrosinase inhibition with the IC50 of 30.000 ppm, which has less effective than kojic acid with IC50 81,10 ppm. Splash mask containing of 1000x IC50, evaluation carried out for 28 days showed that preparations made pharmaceutically stable. Conclusions: In addition, the whitening agent of tangerine peel extract is in the weak category. It is hoped that this research can increase the value of tangerine peel waste.